2008
DOI: 10.1889/1.3069763
|View full text |Cite
|
Sign up to set email alerts
|

47.2: Luminescence Quenching in Blue Fluorescent OLEDs

Abstract: The radical ion of the familiar hole‐transport material NPB (i.e., NPB⋅+) absorbs strongly in the blue region of the spectrum. Therefore, it can quench blue luminescence by Förster energy transfer. A high concentration of NPB⋅+ at the interface between an NPB hole‐transport layer (HTL) and a blue light‐emitting layer (LEL) severely limits the luminescence efficiency of the emitting blue dopant. The efficiency can be improved dramatically by modifying either (a) the anode contact with a thin layer of CuPc, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…As compared to the absorption of neutral MADN, MADN + radical cation shows stronger absorption at 328 nm, 436 nm, 604 nm, 664 nm, and weaker absorption at 361 nm, 377 nm, and 397 nm, respectively. Importantly, there is no significant enhancement of absorption in the range of 450 ~ 550 nm, indicating that MADN + radical cation would not be a strong quencher of green and sky-blue fluorescence as compared to NPB + radical cations [4]. To demonstrate the efficacy of utilizing MADN as HTL, two green OLED devices I and II with structures of ITO/CF x /HTL (60 nm)/Alq 3 : 1% C545T (37.5 nm)/Alq 3 (37.5 nm)/LiF (1 nm)/Al (150 nm) have been fabricated for comparison.…”
Section: Fig 2 Current-voltage (J-v) Characteristics Of Hole-only Dmentioning
confidence: 99%
See 1 more Smart Citation
“…As compared to the absorption of neutral MADN, MADN + radical cation shows stronger absorption at 328 nm, 436 nm, 604 nm, 664 nm, and weaker absorption at 361 nm, 377 nm, and 397 nm, respectively. Importantly, there is no significant enhancement of absorption in the range of 450 ~ 550 nm, indicating that MADN + radical cation would not be a strong quencher of green and sky-blue fluorescence as compared to NPB + radical cations [4]. To demonstrate the efficacy of utilizing MADN as HTL, two green OLED devices I and II with structures of ITO/CF x /HTL (60 nm)/Alq 3 : 1% C545T (37.5 nm)/Alq 3 (37.5 nm)/LiF (1 nm)/Al (150 nm) have been fabricated for comparison.…”
Section: Fig 2 Current-voltage (J-v) Characteristics Of Hole-only Dmentioning
confidence: 99%
“…One of the reasons is that the excess holes would accumulate at HTL/ETL interface and generate NPB + and Alq 3 + radical cations. It has been suggested that exciton quenching at the NPB/Alq 3 interface due to the accumulation of NPB + radical cations at the interface impacts significantly on the current efficiency [3,4]. Moreover, it has also been reported that Alq 3 cationic species would easily be produced when hole carriers exist excessively, resulting in deterioration of device lifetime [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it would be important to establish whether this mechanism more generally yields an appropriate description of the efficiency roll-off. This is urged by experimental evidence that in green-and blueemitting OLEDs TPQ is actually a more long-range process due to Förster resonant energy transfer (FRET) resulting from a triplet-polaron dipole-dipole interaction [9]. The distance (R)-dependent TPQ rate is then given by…”
Section: Introductionmentioning
confidence: 99%
“…However, accurately measuring the extinction spectra of positively or negatively charged molecules is more difficult. Recently, Young et al developed for that purpose an electrochemical method, applicable to dissolved ions [9]. Positively charged 4,4'-bis[1-naphthyl(phenyl)amino]-1,1'-biphenyl (α-NPD) was found to show strong optical absorption with a peak around a wavelength of 480 nm, explaining the occurrence of strong roll-off for blue phosphorescent OLEDs, utilizing α-NPD as a hole-transporting layer in direct contact with the emissive layer.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that charge quenching can play a significant role in determining the current efficiency of EL devices under various device configurations and drive conditions. 14,18,19 It has been suggested that exciton quenching at the NPB/Alq interface due to the accumulation of NPB + radical cations 20,21 at the interface largely determines the current efficiency. In the case of the bilayer NPB/Alq device, the electric field in the NPB layer is negligible under forward bias, and the NPB/Alq …”
mentioning
confidence: 99%